Pre-Planarized Triphenylamine-Based Linear Mixed-Valence Charge-Transfer Systems - Krug, Marcel; Fröhlich, Nina; Fehn, Dominik; Vogel, Alexander; Rominger, Frank; Meyer, Karsten; Clark, Timothy; Kivala, Milan; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2021)
Three linear dimers with two redox-active planarized triphenylamines were synthesized and their structures verified by X-ray crystallography. Their radical cations, which exhibit electron self-exchange between the two redox centers, are of great interest. This process was thoroughly investigated by means of electron paramagnetic resonance spectroscopy, absorption spectroscopy, and (time-dependent) density functional theory calculations. A comparison of the key parameters of electron transfer with non-planarized nitrogen-centered building blocks emphasizes the impact of using redox centers with low internal reorganization energies. However, the distance-dependence attenuation factor of the super-exchange mechanisms remains similar.
CRIS-Team WoS Importer:2021-02-26